Policies and practices for the professionalization of the teaching profession in the late Ottoman Empire (1839-1920) - Çiydem, Erol (Informa UK Limited, 2021)
Studies in the context of the professionalisation of the teaching profession in Turkey mainly focus on policies and practices for teacher training in the Republican Period. However, the practices a...
Keywords: 4. Education